The Provisions Governing The Free Zones In Syria And Their Role As A Tool To Attract Foreign Investment - عثمان, سلمان; يونس, حيدر (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Free zones and development zones have played a large and important role in creating an investment climate, attracting Arab and foreign capital, developing local industries and creating opportunities for employment, in addition to their significant impact on global trade, and the objectives for which free zones were established are to attract foreign capital to invest in the country, Increasing the volume of the country's exports of free zone products and reducing the volume of imports by meeting the needs of the local market for products from these zones instead of relying on abroad. The research objectives are evident through researching the concept of free zones in Syria and the controls of investment in them and studying the laws governing the Syrian free zones in attracting foreign investments. The researcher relied on the descriptive and analytical approach of texts and legal articles related to foreign investments in the Syrian free zones, and studying indicators related to the development of foreign investments during Over the past years.